Augmented Reality for Introducing Fuel Cell as Electrochemical Energy Conversion on Vocational School - Sendari, Siti; Jiono, Mahfud; Diantoro, Markus; Puspitasari, Poppy; Surjanto, Heru; Nur, Hadi (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Nowadays, one kind of promising energy is fuel cell technology, which produces electricity while hydrogen gas flows from anode to cathode through a membrane. A single fuel cell can be integrated in series as a fuel cell stack. It shows electro-chemical process, where the gas flows from the anode to cathode through a membrane and acts as protons and electrons. Students have plenty of difficulties to understand the concept of the electro-chemical process. Thus, this paper studies the effectiveness of usability of the developed augmented reality (AR) technology for bridging the difficulties in electrochemical process, especially fuel cell energy conversion. AR technology is used as an accomplished tool of a conventional book, where students can learn deeply about the process, such as practicing steps and problem solving using animation. The implementation results show that the developed AR can help students enjoy to study fuel cell energy conversion, which means that the developed AR can support learning process effectively